Analisis Kebutuhan Bahan Ajar dalam Pembelajaran Metode Penelitian Terapan di Program Studi Kosmetik dan Perawatan Kecantikan - Armandari, Mari Okatini; Ambarwati, Neneng Siti Silfi; Hidayah, Nurul (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
Applied research methods strengthen the relationship between theory and practice in the field of cosmetics and beauty care, which is important for understanding and development in higher education. The purpose of this study was to analyze the need for teaching materials in learning applied research methods in cosmetic and beauty care study programs. This study used the Systematic Literature Review (SLR) method guided by PRISMA. A total of 298 articles were collected from Google Scholar, ScienceDirect, and Taylor and Francis, and after applying predetermined criteria, 27 relevant articles were included for analysis. The findings of the study indicate that teaching materials have an important role in learning, and teaching materials will be effectively used if they meet the eligibility requirements that must be met, the implication is that it is important to explore strategies for developing new teaching materials for learning applied research methods in cosmetic and beauty care study programs to improve student understanding.